Utilizing charge reconfigurations of quantum-dot cells in building blocks to design nanoelectronic adder circuits. (September 2020) - Abutaleb, M.M.
Highlights: Implementation of cell-based three-input XOR and two-to-one multiplexer as ultra-efficient building blocks in QCA. They are implemented based on Coulombic interactions between quantum-dot cells. They are really compact and novel, designed using only very few QCA cells. They are used for implementing full-adders and four-bit adders to demonstrate their performance. Abstract: In the quantum-dot cellular automata (QCA) nanotechnology, the cell-based building block can be designed by utilizing the charge reconfiguration of quantum-dot cells in order to achieve the desired function with optimal implementation. In this paper, new advanced nanostructures based on quantum-dot cells are introduced to three-input XOR gate and two-to-one multiplexer, which can be considered in addition to the conventional majority voter as basic building blocks used in implementing well-optimized QCA circuits. Consequently, these blocks are used in this paper to implement new single-layer QCA full-adders and four-bit adders as motivational applications. Moreover, an innovative design approach of full-adder is proposed to avoid the presence of inputs surrounded by QCA cells and to prevent the use of crossovers when building multi-bit adders. The proposed QCA layouts are simulated and evaluated as results indicate that proposed designs are superior to the previous designs in the literature. Graphical abstract: Image, graphical abstract